High Shedding Potential and Significant Individual Heterogeneity in Naturally-Infected Alpine ibex (Capra ibex) With Brucella melitensis - Lambert, Sébastien; Gilot-Fromont, Emmanuelle; Freycon, Pauline; Thébault, Anne; Game, Yvette; Toïgo, Carole; Petit, Elodie; Barthe, Marie-Noëlle; Reynaud, Gaël; Jaÿ, Maryne; Garin-Bastuji, Bruno; Ponsart, Claire; et al. (Frontiers in Microbiology, 2018)
Wildlife reservoirs of infectious diseases raise major management issues. In Europe, brucellosis has been eradicated in domestic ruminants from most countries and wild ruminants have not been considered important reservoirs so far. However, a high prevalence of Brucella melitensis infection has been recently identified in a French population of Alpine ibex (Capra ibex), after the emergence of brucellosis was confirmed in a dairy cattle farm and two human cases. This situation raised the need to identify the factors driving the persistence of Brucella infection at high prevalence levels in this ibex population. In the present paper, we studied the shedding pattern of B. melitensis in ibex from Bargy Massif, French Alps. Bacteriological examinations (1 to 15 tissues/samples per individual) were performed on 88 seropositive, supposedly infected and euthanized individuals. Among them, 51 (58%) showed at least one positive culture, including 45 ibex with at least one Brucella isolation from a urogenital sample or a lymph node in the pelvic area (active infection in organs in the pelvic area). Among these 45 ibex, 26 (30% of the total number of necropsied animals) showed at least one positive culture for a urogenital organ and were considered as being at risk of shedding the bacteria at the time of capture. We observed significant heterogeneity between sex-and-age classes: seropositive females were most at risk to excrete Brucella before the age of 5 years, possibly corresponding to abortion during the first pregnancy following infection such as reported in the domestic ruminants. The high shedding potential observed in young females may have contributed to the self-sustained maintenance of infection in this population, whereas males are supposed to play a role of transmission between spatial units through venereal transmission during mating. This heterogeneity in the shedding potential of seropositive individuals should be considered in the future to better evaluate management scenarios in this system as well as in others.